The Associations Between Happiness Motives and Well-Being in China: The Mediating Role of Psychological Need Satisfaction and Frustration - Lin, Li; Chan, Hoi-Wing (Frontiers in Psychology, 2020)
Happiness can be pursued based on hedonic motives (i.e., seeking pleasure and comfort) and/or eudaimonic motives (i.e., seeking to develop and make the best use of the self). Substantial studies have found that hedonic and eudaimonic motives relate to well-being outcomes in different ways. However, these findings were predominately based on Western samples while study is scanty about the relationship between happiness motives and well-being outcomes in Eastern cultures. Furthermore, little is known about the mechanisms that underlie these associations. To address these gaps, we conducted two studies based on Chinese college students. In Study 1 (N = 301), structural equation modeling demonstrated that eudaimonic motives were positively associated with life satisfaction and meaning in life, but hedonic motives were not significantly associated with either indicator of well-being. In Study 2 (N = 526), structural equation modeling showed that (1) hedonic motives had an indirect effect on life satisfaction through need frustration; (2) eudaimonic motives had indirect effects on life satisfaction and meaning in life through need satisfaction and need frustration. These findings highlight the important roles that the satisfaction and frustration of basic psychological needs play in translating happiness motives into well-being outcomes.